MECHANICAL PROPERTIES BETON AGROPOLIMER ABU SEKAM PADI DENGAN AKTIVATOR SODIUM SILIKAT DAN SODIUM HIDROKSIDA - Yusnar, Cut; Ruhana, Ruhana; YH, Sulaiman (Universitas Bengkulu, 2017)
Rice Husk Ash usually used as pozzolanic material admixtures that have been used for Geopolimer concrete. This study report on the behavior on mechanical properties (compressive and flexural) of rice husk ash geopolimer concrete using activator sodium silicate and sodium hydroxide with variation comparison of sodium silicate to sodium hydroxide was 0,25; 0,1; and 1,25. Concrete testing included the determination of compressive and flexural properties. It was shown that the behavior of compressive properties of comparison of sodium silicate to sodium hydroxide 1,0 was the optimum result and the behavior of flexure properties gotoptimum result on the comparison of sodium silicate and sodium hydroxide was 1,25.